ISOLATION AND STRUCTURAL ELUCIDATION OF PHENOLIC COMPONENTS FROM CALOTROPIS PROCERA (AIT) AND EVALUATION OF INSECTICIDAL ACTIVITY - Bellaouar Nacira; Bouziane Mebarka; Laichi Yacine; Hadjadj Mohamed; Hammoudi Roukia; Hadj Mahammed Mahfoud (Journal of Animal and Plant Sciences, 2023)
The identification and characterization of two phenolic compounds from the ethyl acetate (EtAc) extract of Calotropis procera aerial parts were performed using chromatographic and spectroscopic methods namely Thin Layer Chromatography (TLC), Preparative Thin Layer Chromatography (PTLC), High-Performance Liquid Chromatography (HPLC), Infrared spectroscopy (FT-IR) and Nuclear Magnetic Resonance (1H-NMR, 13C-NMR).Two major compounds were isolated to be the 3, 3’, 4’, 5, 7-pentahydroxy flavones-3-rutinoside (Rutin) and 3,4,5-trihydroxybenzoic acid(Gallic acid), the results were confirmed by comparison with standards. In addition, the insecticidal activity of these isolated compounds was determined against Parlatoria blancharditarg individuals, 71.73% and 59.44% mortality were recorded at 0.5 mg/ml of Rutin and Gallic acid respectively, after 24 h of treatment; whereas, the larval stages were the most sensitive to Rutin treatment (LD50 equal to0.10 mg/ml for 1st larva and 0.18 mg/ml for 2nd larva).
Keywords: Calotropis procera; Rutin; Gallic acid; Parlatoria blanchardi